Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1007/bf01666527
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative and quantitative analysis of the response of the retinal ganglion cell soma after stretch injury to the adult guinea-pig optic nerve

Abstract: The development of a model for focal axonal injury in the optic nerve of the adult guinea-pig has allowed a qualitative and quantitative analysis of the response of the retinal ganglion cell soma to this type of injury. Large and medium sized retinal ganglion cells show classic 'central chromatolysis' in about 30% of ganglion cells between three and seven days after injury, a high proportion of which undergo degeneration between seven and 14 days. Small ganglion cells and small neurons do not demonstrate any m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 51 publications
1
22
2
Order By: Relevance
“…This, coupled with the observation of lengthening of the axotomized process at 48 hr and the overall reduction in axonal swelling size at the same time, argues that those neurons sustaining TAI are not dying but rather may be attempting a reparative response. Using a dissimilar optic nerve stretch injury model, Maxwell et al (1994) alluded to a similar possibility in a subpopulation of injured neurons, whereas another group (Emery et al, 2000) has recently identified TBI-induced expression of markers associated with neuronal regeneration in the same brain regions found herein to sustain perisomatic TAI.…”
Section: Discussionmentioning
confidence: 90%
“…This, coupled with the observation of lengthening of the axotomized process at 48 hr and the overall reduction in axonal swelling size at the same time, argues that those neurons sustaining TAI are not dying but rather may be attempting a reparative response. Using a dissimilar optic nerve stretch injury model, Maxwell et al (1994) alluded to a similar possibility in a subpopulation of injured neurons, whereas another group (Emery et al, 2000) has recently identified TBI-induced expression of markers associated with neuronal regeneration in the same brain regions found herein to sustain perisomatic TAI.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast to crush or cut injury where axons and surrounding glial cells are acutely damaged, diffuse injury to the nervous system results in slow axonal disconnections with distinct morphological characteristics (Maxwell et al, 1994). Mechanical strain applied to mammalian axons has previously been shown to result in alterations in the properties of the axolemma, leading to Fig.…”
Section: Subsets Of Rgcs Increase Gap-43 and ␣-Tubulin Mrna Levels Afmentioning
confidence: 99%
“…39,78,79 Owing, in part, to the isolated nature of the white matter injury, these models have proven very useful in evaluating ultrastructural changes in axons after trauma as well as identifying pathological chemical cascades that may represent important therapeutic targets. 34,39,47,[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] These models, however, are not widely used or practical for high-throughput therapy evaluation. Nonetheless, they represent a potential stepwise bridge between in vitro and in vivo therapy development.…”
Section: Lissencephalic Animal Models Of Taimentioning
confidence: 99%